2023
DOI: 10.3390/jcm12062235
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Review in Cardiac Arrest: The 2022 Randomized Controlled Trials

Abstract: Cardiac arrest, one of the leading causes of death, accounts for numerous clinical studies published each year. This review summarizes the findings of all the randomized controlled clinical trials (RCT) on cardiac arrest published in the year 2022. The RCTs are presented according to the following categories: out-of- and in-hospital cardiac arrest (OHCA, IHCA) and post-cardiac arrest care. Interestingly, more than 80% of the RCTs encompassed advanced life support and post-cardiac arrest care, while no studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 68 publications
0
0
0
Order By: Relevance
“…Cardiac arrest stands as a formidable challenge in global health, currently ranking as the third leading cause of death worldwide [1]. The recent EuReCa TWO study reported an incidence of out-of-hospital cardiac arrest (OHCA) in Europe of 89 events per 100,000 inhabitants per year.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac arrest stands as a formidable challenge in global health, currently ranking as the third leading cause of death worldwide [1]. The recent EuReCa TWO study reported an incidence of out-of-hospital cardiac arrest (OHCA) in Europe of 89 events per 100,000 inhabitants per year.…”
Section: Introductionmentioning
confidence: 99%
“…The number of trials in the field of out-of-hospital cardiac arrest (OHCA) has grown exponentially throughout the last decade, largely with a focus on increased survival as a key metric for the effectiveness of interventions [1]. In 2018, in an effort to clarify meaningful outcomes for ongoing research, the International Liaison Committee on Resuscitation published the Core Outcome Set for Cardiac Arrest (COSCA) in Adults [2].…”
Section: Introductionmentioning
confidence: 99%
“…Postcardiac arrest syndrome (PCAS) results in high morbidity and mortality due to a series of life-threatening complications such as multiorgan failure and neurological damage [1][2][3]. PCAS is a type of global ischemic reperfusion injury that occurs after the return of spontaneous circulation (ROSC) by a mechanism similar to one in systemic inflammatory response syndrome (SIRS) or sepsis [4,5].…”
Section: Introductionmentioning
confidence: 99%